Wisata Dolanan: Pengembangan Wisata Tematik Berbasis Budaya di Kampung Biru Arema (KBA) Kota Malang - Hamamah Hamamah; Agus Suman; Fredy Nugroho Setiawan; Rizki Nufiarni (Jurnal Surya Masyarakat, 2020)
This article describes efforts to develop one of the tourism areas in Kampung Biru Arema (KBA), namely the “Dolanan” (Traditional Games) Area. The “Dolanan” Area is one of the five tourism areas in KBA which is being developed collaboratively between a team from the Faculty of Cultural Studies Universitas Brawijaya and local community. The development of the area is based on local wisdomby introducing a variety of traditional games, namely: “tapak gunung (engklek)”, “congklak (dakon)”, and “gasing” (spinning tops)presented with modern designs so that they are acceptable, especially for the young generation. The “Dolanan”Area is expected to become a distinctive KBA identity as well as a medium for educational tourism that introduces the richness of local culture in the packaging of community-based tourism.